ASSESMENT IN TEACHING ENGLISH - Firdaus Syahril (Deiksis, 2012)
Assessment is an activity that can not be separated from educational activities which carried out should be followed activities by assessment activities. Assessment purpose is not only assessing students’ work but also using as a feed back of rating of the teaching activities carried out. Assessment of students must do continuously during the course of teaching and learning activities. Assessment dealing with quantitative and qualitative data, while measurements are only part of appraisal is always associated with qualitative data. Assessment requires quantitative data from measurements. Conversely, the measurement is also very tied to the special assessment issues related to the objectives and criteria that are used. Assessment is the process of obtaining and using information to make consideration as the basic of information retrieval. Thus, there are three components of assessment namely information, consideration, and decisionsKey words: Assessment and measurement.